Situationality in teaching controversial topics: (When) does controversial equal difficult? - Wansink, Bjorn; Mogutov, Mikhail; Damhuis, Koen; Bronkhorst , Larike (JSSE - Journal of Social Science Education, 2024)
Most teachers in the Netherlands do not report difficulty in discussing the most controversial topics. Anti-muslimism, COVID vaccination, and integration of ethnic minorities are perceived as relatively difficult topics to discuss. High teacher self-efficacy and school support are related to reported ease in discussing all controversial topics. Specific controversial topics are considered more challenging to discuss in diverse classrooms in terms of SES and ethnicity. Controversial topics are perceived as more difficult to discuss in vocational educational tracks. Purpose: This study examines what controversial topics teachers in the Netherlands perceive as difficult to discuss and if and how this difficulty is related to teachers’ background characteristics and context characteristics. Methodology: 1034 secondary school teachers filled in an online questionnaire, and structural equation modelling (SEM) was used to explore the relationships among variables. Findings: The findings indicate that recent topics with a direct large impact on students’ lives and society, like COVID vaccination, are perceived as most difficult to discuss. With more perceived school support and high self-efficacy teachers report more ease to discuss controversial topics. Yet, reported difficulty to discussing controversial topics is also partially context- and person-specific, involving (among others) classroom composition, school subject and teacher’s age. Practical implications: This study can inform the development of subject and context-specific teaching materials and training programs in civic and democratic education.